The resting membrane potential of hSC-CM in a syncytium is more hyperpolarised than that of isolated cells. Issue 1 (1st January 2021) - Van de Sande, Dieter V.; Kopljar, Ivan; Maaike, Alaerts; Teisman, Ard; Gallacher, David J.; Bart, Loeys; Snyders, Dirk J.; Leybaert, Luc; Lu, Hua Rong; Labro, Alain J.
ABSTRACT: Human-induced pluripotent stem cell (hiPSC) and stem cell (hSC) derived cardiomyocytes (CM) are gaining popularity as in vitro model for cardiology and pharmacology studies. A remaining flaw of these cells, as shown by single-cell electrophysiological characterization, is a more depolarized resting membrane potential (RMP) compared to native CM. Most reports attribute this to a lower expression of the Kir2.1 potassium channel that generates the IK1 current. However, most RMP recordings are obtained from isolated hSC/hiPSC-CMs whereas in a more native setting these cells are interconnected with neighboring cells by connexin-based gap junctions, forming a syncytium. Hereby, these cells are electrically connected and the total pool of IK1 increases. Therefore, the input resistance (Ri) of interconnected cells is lower than that of isolated cells. During patch clamp experiments pipettes need to be well attached or sealed to the cell, which is reflected in the seal resistance (Rs), because a nonspecific ionic current can leak through this pipette-cell contact or seal and balance out small currents within the cell such as IK1 . By recording the action potential of isolated hSC-CMs and that of hSC-CMs cultured in small monolayers, we show that the RMP of hSC-CMs in monolayer is approximately −20 mV more hyperpolarized compared to isolated cells. Accordingly, adding carbenoxolone, a connexin channel blocker, isolates the cell that is patch clamped from its neighboring cells of the monolayer and depolarizes the RMP. The presented data show that the recorded RMP of hSC-CMs in a syncytium is more negative than that determined from isolated hSC/hiPSC-CMs, most likely because the active pool of Kir2.1 channels increased.